Fragile Indonesia, Resilient Indonesia: Understanding Indonesia's Position in The Global War For Talent - Asep Sukmayadi; Avanti Fontana; Margaretha Hanita; Solikhah Yuliatiningtyas (Proceedings of International Conference on Science, Education, and Technology, 2026)
This paper examines the strategic meaning of Indonesia’s position in the phenomenon commonly referred to as the “global war for talent”. By reassessing Indonesia’s position measured by Global Talent Competitiveness Index (GTCI) in year of 2020-2023, this study discuss the strategic significance of Indonesia’s position in a broader view. Indonesia’s position in the Global Talent Competitiveness Index reflects a strategic paradox. On the one hand, Indonesia possesses significant demographic potential and abundant human resources; on the other hand, the country continues to face structural vulnerabilities in global talent competitiveness. The findings therefore indicate that Indonesia’s relatively modest position in global talent competitiveness is not merely an educational issue, but also reflects broader structural challenges. In this context, global talent competitiveness should be understood as an integral dimensions of national resilience, since the capacity to develop, attract, and retain talent increasingly determines a nation’s ability to survive and compete in the global arena. This study argues that strengthening Indonesia’s talent competitiveness requires an integrated national talent management in a long-term national resilience frameworks. Therefore, the discourse on global talent competitiveness and talent development should not be viewed solely as a sectoral educational agenda, but as a strategic geopolitical and national resilience issue in midst of an increasingly volatile and uncertain global environment.